Meandering as learning: Co-creating care with Camissa Oceans in higher education - Martin, Aaniyah; Peers, Joanne; Giorza, Theresa (Critical Studies in Teaching and Learning, 2023)
This paper meanders with students from the Centre for Creative Education to understand care and our relationship with Camissa. The authors explore Slow scholarship and research-creation frameworks that disrupt practices which remain entrenched in colonial, anthropocentric and patriarchal systems. Apartheid is felt by Black and Brown bodies through exclusions from the ocean and other spaces. This paper explores how enquiries and innovations open spaces for lost care practices to be re-membered.